Mantle plumes beneath the South Pacific superswell revealed by finite frequency P tomography using regional seafloor and island data. Issue 22 (26th November 2016) - Obayashi, M.; Yoshimitsu, J.; Sugioka, H.; Ito, A.; Isse, T.; Shiobara, H.; Reymond, D.; Suetsugu, D.
Abstract: We present a new tomographic image beneath the South Pacific superswell, using finite frequency P wave travel time tomography with global and regional data. The regional stations include broadband ocean‐bottom seismograph stations. The tomographic image shows slow anomalies of 200‐300 km in diameter beneath most hot spots in the studied region, extending continuously from the shallow upper mantle to 400 km depth. Narrow and weak slow anomalies are detected at depths of 500–1000 km, connecting the upper mantle slow anomalies with large‐scale slow anomalies with lateral dimension of 1000–2000 km prevailing below 1000 km depth down to the core‐mantle boundary. There are two slow anomalies around the Society hot spot at depths shallower than 400 km, which both emerge from the same slow anomaly at 500 km depth. One of them is located beneath the Society hot spot and the other underlies 500 km east of the Society hot spot, where no volcanism is observed. Key Points: P wave tomography shows localized slow anomalies in the upper 400 km of the mantle beneath most of the South Pacific hot spots Large‐scale slow anomalies extend from a depth of 1000 km to the core‐mantle boundary A narrow and weak slow anomaly found at 500‐1000 km depths connects upper mantle slow anomalies with large‐scale anomalies below 1000 km